Blockchain Usage in Smart Cities: A Systematic Review - Loss, Stefano; Cacho, Nélio; Lopes, Frederico (Anais do Colóquio em Blockchain e Web Descentralizada (CBlockchain); 2023: Anais do I Colóquio em Blockchain e Web Descentralizada, 2023)
Blockchain has been widely used to store decentralized and secure cryptocurrency transactions (for instance, Bitcoin solution). On the other hand, smart city applications are concerned with how data and services can be stored and shared securely. In this regard, this paper investigates the use of blockchain in the context of smart city environments. We conducted a systematic review to understand how blockchain could be used in smart city scenarios. This review resulted in a set of important requirements to meet the needs of the blockchain in the context of smart cities.